A spatial assessment of high-resolution drainage characteristics and roadway safety during wet conditions. (August 2021) - Crimmins, Michael; Park, Seri; Smith, Virginia; Kremer, Peleg
Abstract: Much of the research regarding traffic crashes considers various geometric roadway features; however, ever-evolving urban watersheds and climate change increasingly impact roadway conditions. Little research has focused on the relationship between high-resolution drainage characteristics and the spatial distribution of crashes. This study incorporated local environmental and drainage risk factors in assessing network safety performance using spatial analysis techniques. Kernel density surfaces and the Local Getis Ord Gi* statistics were used to identify and visualize locations prone to experiencing crashes during wet conditions. Spatial regression modelling was used to link crashes to environmental and traffic risk factors across a citywide network. Proof-of-concept for this framework is demonstrated in the City of Philadelphia, Pennsylvania using publicly available spatial data. The results of this study show a relationship between local drainage, environmental characteristics, and wet crash distribution, providing novel insight into roadway safety during wet conditions. Highlights: This study incorporated local environmental and drainage risk factors to assess network safety performance using spatial analysis techniques. Spatial regression modelling was used to link crashes to environmental and traffic risk factors across a citywide network. This study links drainage, environmental characteristics, and crashes, providing novel insight into roadway safety during wet conditions.